Clinical significance of pulmonary hypertension in interstitial lung disease: A consensus statement from the Pulmonary Vascular Research Institute's innovative drug development initiative—Group 3 pulmonary hypertension. (22nd August 2022) - Nikkho, Sylvia M.; Richter, Manuel J.; Shen, Eric; Abman, Steven H.; Antoniou, Katerina; Chung, Jonathan; Fernandes, Peter; Hassoun, Paul; Lazarus, Howard M.; Olschewski, Horst; Piccari, Lucilla; Psotka, Mitchell; et al.
Abstract: Pulmonary hypertension (PH) has been linked to worse outcomes in chronic lung diseases. The presence of PH in the setting of underlying Interstitial Lung Disease (ILD) is strongly associated with decreased exercise and functional capacity, an increased risk of hospitalizations and death. Examining the scope of this issue and its impact on patients is the first step in trying to define a roadmap to facilitate and encourage future research in this area. The aim of our working group is to strengthen the communities understanding of PH due to lung diseases and to improve the care and quality of life of affected patients. This introductory statement provides a broad overview and lays the foundation for further in‐depth papers on specific topics pertaining to PH‐ILD.